The psychological factors which contribute to pre-competition insomnia in sprinters - Li, L.; Fang, C. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Sleeplessness before competition is a special type of insomnia. The probability of it occurring is 60%, which is higher than the risk in the general population. There is little research on this topic. The purpose of the study was to investigate the relevant factors impacting on sleep disorders of sprinters, and to provide effective preventive and treatment measures to reduce the incidence of insomnia. It was expected that the results will be useful to enhance the physical and mental health of athletes. Methods The subjects were 15, 100m sprinters from the Shaanxi track team and 15 100m sprinters from the Xi'an Sports Institute. The research methods included document analysis, questionnaire, measurement of athletes` anxiety before competitions, a coping style survey, and a Type A questionnaire (TABO). SPSS was used to perform a t-test, x2 test, and regression analysis. Results The results indicated that 53.3% of sprinters experienced insomnia before competitions. Four factors affecting insomnia in sprinters were identified. The first factor was named "Depressed factor of anxiety" This characteristic was worth 2.903 and its accumulated contribution was 69.56%). The second factor was named "Coping" (this characteristic was worth 3.383 and its accumulated contribution was 46.43%). The third factor was named "Societal supports" (this characteristic was worth 6.737 and its accumulated contribution led to 34.68%). The final factor was named "A type character characteristic" (which was worth 5.738 and had an accumulated contribution of 17.64%) Discussion/ Conclusions The average score on the anxiety scale, SAS, was 49.02 ±10.57 for the insomnia group and 41.7 ±7.98 for the control group. The difference between these means was found to be significant (p<0.01). A multivariate regression analysis was used to examine the relationship between source of excitement and sleep. The analysis used the anxiety score as the dependent variable that responded to 36 kinds of independent variables. These were notable sources of excitation including the competition experience, competitive motivation, competition target, self-confidence, drive for success, expectations of the sports team and the attitudes toward success or failure of both the athlete and the coach. Nine factors impacted on the level of anxiety. The difference was very notable between the insomnia group and the control group in for "Coping" actively (p <0.01), but was not significant for "Coping" inactively (p > 0.05). The level of active coping was obviously lower for the insomnia group compared with the control group. The results indicate that the insomnia group were relatively poorer in their response to excitation. There was a considerable difference in subjective support and the use of societal support between the insomnia group and the control (p<0.01). There was no notable difference in objective support (p> 0.05). The results indicated that the incidence of insomnia in athletes with an A type character was 70% (11/16). The average total score for athletes with A type character and TH factor was higher than the control group (p <0.05 ~ 0.01). Overall the results indicate that athletes with an A type personality, who feel though they are being rushed are at most risk of insomnia.